Systematics of azimuthal asymmetries in heavy ion collisions in the 1A GeV regime - Reisdorf, Willibrord; Benabderrahmane, Mohamed Lotfi; Herrmann, Norbert; Merschmeyer, Markus; Piasecki, Krzysztof; Stockmeier, Matthias (Nuclear physics. A, Nuclear and hadronic physics, 2012)
Using the large acceptance apparatus FOPI, we study central and semi-central collisions in the reactions (energies in A GeV are given in parentheses): 40Ca+40Ca (0.4, 0.6, 0.8, 1.0, 1.5, 1.93), 58Ni+58Ni (0.15, 0.25, 0.4), 96Ru+96Ru (0.4, 1.0, 1.5), 96Zr+96Zr (0.4, 1.0, 1.5), 129Xe+CsI (0.15, 0.25, 0.4), 197Au+197Au (0.09, 0.12, 0.15, 0.25, 0.4, 0.6, 0.8, 1.0, 1.2, 1.5). The observables include directed and elliptic flow. The data are compared to earlier data where possible and to transport model simulations. A stiff nuclear equation of state is found to be incompatible with the data. Evidence for extra-repulsion of neutrons in compressed asymmetric matter is found.